Fecundity of the parental and fitness of the F1 populations of corn earworm from refuge ears of seed blend plantings with Genuity® SmartStax™ maize. (October 2019) - Guo, Jianguo; Yang, Fei; Brown, Sebe; Kern, David; Head, Graham P.; Price, Paula A.; Niu, Ying; Huang, Fangneng
Abstract: Seed blend, also called 'refuge-in-the-bag (RIB)', has been used as a refuge strategy to generate susceptible insect populations for Bt maize resistance management in the U.S. Corn Belt. A major concern related to the use of RIB is the cross-pollination of maize plants that cause Bt protein expression in the kernels of refuge ears. Bt protein expression in the refuge ears can negatively affect the insect populations on refuge plants, especially for ear feeders such as the corn earworm, Helicoverpa zea (Boddie). The current study investigated the reproduction of three populations of H. zea collected from a pure stand of non-Bt maize and the refuge ears of 90:10% (Bt:non-Bt seeds) and 80:20% RIBs, as well as the growth, development and reproduction of the F1 offspring of the three populations. The biological parameters measured for the F1 offspring included neonate-to-pupa developmental time, pupal weight, neonate-to-adult survival rate, egg production, and net reproductive rate of the adults on meridic diet. Reproduction of the parents and the fitness of the F1 offspring were similar among the three populations and were not significantly affected by the seed blending patterns. Information generated from this study will be useful in assessing if RIB is a suitable method for Bt maize resistance management in the southern U.S. Highlights: Parental fecundity of H. zea populations from three seed mixes of non-Bt and Bt corn were evaluated. Survival, development, and reproduction of the F1 filial populations were measured on meridic diet. Reproduction of the parents and the relative fitness of the F1 offspring were not affected by Bt protein expression in refuge ears. Information generated will improve our assessment of the suitability of seed mix for Bt corn IRM.